Focus on photographing people - Kamps, Haje Jan (Focal Press, 2011)
Taking good photographs of people is a combination of many factors: What is the best light for the subject? How should they stand? What aperture should you use for maximum impact? This easy-to-follow, highly visual guide to portraiture explains the technical and aesthetic considerations of creating great images. Step-by-step instruction, tips from an experienced professional photographer, project assignments and gorgeous photography make learning how to take good photos of people quick and easy. Aimed at beginners or amateurs toting a DSLR and wanting pointers on how to make their people photography really shine, this book offers the basics on composition, lighting, posing, street photography and post-production techniques in a fun and conversational manner. - Highly visual guide to the most popular subject - people - Tip boxes, summaries and assignments make learning the techniques easier - Not just a photo technique book - advice on posing, backgrounds and lighting to make portraits stand out.